New species and new records of Manota Williston (Diptera, Mycetophilidae) from Thailand - Hippa, Heikki (Zootaxa, 2009)
The following 10 new species are described: Manota avita, M. chelapex, M. chi, M. epigrata, M. obtecta, M. prisca, M. seducta, M. subferrata, M. tetrachaeta, and M. vesicaria. New records of the following species are given: Manota aconcinna Hippa, M. acutangula Hippa, M. ancylochaeta Hippa, M. clavulosa Hippa, M. collina Hippa, M. cristata Hippa, M. globigera Hippa, M. inflata Hippa, M. oblonga Hippa, M. oligochaeta Hippa, M. ovata Hippa, M. pectinata Hippa, M. pellii Hippa, M. perlobata Hippa, M. perpusilla Hippa, M. planilobata Hippa, M. procera Hippa, M. roslii Hippa, and M. simplex Hippa. The taxonomy of M. perpusilla, M. planilobata and M. procera is discussed and new descriptions of the hypopygia of the two former species are given.